1993
DOI: 10.1177/039139889301600907
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Agents and Blood Pressure Regulation in Sequential Ultrafiltration and Hemodialysis

Abstract: Hypotension is a common and sometimes dangerous side effect of hemodialysis. Its etiology is multifactorial and largely unknown. Earlier studies on the role of endogenous blood pressure regulating agents such as catecholamines and renin have rendered conflicting results. We studied the influence of ultrafiltration and isovolemic hemodialysis separately on the plasma concentrations of the following blood pressure regulating agents: adrenaline, noradrenaline, dopamine, neuropeptide Y, calcitonin gene-related pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The sympathetic activation and consequently increased local levels of catecholamines might also stimulate generation of ET-1 [1]. Odar-Cederloef et al [17]observed falls of neck vein pressure by about 1.2 mm Hg and rises in circulating norepinephrine by 30% during isolated ultrafiltration with fluid removal of about 2.1 liters. Kinet et al [18]reported reduction of mean pulmonary capillary wedge pressure by 9.4 mm Hg after hemodialysis, whereas tilting-induced reductions of central venous pressure of about 3.4 mm Hg produced significant elevations of circulating ET-1 [19].…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic activation and consequently increased local levels of catecholamines might also stimulate generation of ET-1 [1]. Odar-Cederloef et al [17]observed falls of neck vein pressure by about 1.2 mm Hg and rises in circulating norepinephrine by 30% during isolated ultrafiltration with fluid removal of about 2.1 liters. Kinet et al [18]reported reduction of mean pulmonary capillary wedge pressure by 9.4 mm Hg after hemodialysis, whereas tilting-induced reductions of central venous pressure of about 3.4 mm Hg produced significant elevations of circulating ET-1 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in which UF-only was preceded or followed by isovolumic HD showed divergent results regarding the course of AVP [2,39,40,48,59]. It is beyond the scope of this article to discuss these studies in detail.…”
Section: Other Dialysis Techniquesmentioning
confidence: 98%
“…Plasma AVP levels in patients varied widely, with some studies reporting pre-HD plasma AVP levels above the concentration regarded as the upper level of normal of 4 pg/ml [2,16,24,25,35,37,38,39,40,41,45,46,47,48,49,50,51,52,53,54], while others found pretreatment plasma AVP levels around or below 4 pg/ml [32,33,34,43,44,55,56,57] (fig. 3a).The variation in pretreatment plasma AVP levels might be due to analytical variation resulting from the use of different assays.…”
Section: Plasma Vasopressin Levels In Dialysis Patients and Healthy Imentioning
confidence: 99%
See 2 more Smart Citations